Efektivitas Proper Body Mechanics terhadap Kemampuan Mobilitas Lansia dengan Kondisi Nyeri Punggung Bawah - Sanghiko Pramesti, Hudaya; Kurniawan, Hendri (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Elderly people are prone to low back pain (LBP). LBP can cause mobility disorders. One approach to overcoming pain in LBP is to apply Proper Body Mechanics (PBM). Objectives: The study aims to examine the effectiveness of PBM implementation on the mobility ability of elderly people with LBP. Methods: This quantitative study used a pre-experimental design with one group pre and post-test. The sampling technique used was purposive sampling with a sample size of 30 elderly people. The Tinetti Performance-Oriented Mobility Assessment (POMA) instrument measured the research variables. Data were analyzed using the Wilcoxon and N-gain tests using SPSS version 25. Results: The majority of the samples were middle-aged elderly (43.3%), female (56.7%), normal weight (40%), high pain level (56,7%) and had moderate mobility disorders (86,7%). The application of PBM increased mobility ability by 76.7%. The results of the Wilcoxon test obtained a p-value <0.005 with an N-Gain score = 0.65 (moderate effectiveness). Conclusion: The implementation of PBM effectively improves the mobility ability of elderly people with LBP. Keywords : elderly, mobility, PBM, LBP